2014
DOI: 10.1002/jhbp.115
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical impact of the remnant pancreatic volume and infectious complications on the development of nonalcoholic fatty liver disease after pancreaticoduodenectomy

Abstract: After PD, RPV and status of postoperative infection paradoxically influenced the development of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
55
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 31 publications
10
55
2
Order By: Relevance
“…This is in agreement with previous reports revealing that postoperative hepatic steatosis after PD occurs more commonly in females and that females with hepatic steatosis may have a poor response to PERT with high-dose pancrelipase. 20,24 Overall, according to population-based studies, conventional hepatic steatosis is more common in men; however, women have a higher risk of advanced fibrosis. 36 Previous epidemiological studies revealed that postmenopausal women have increased risks of insulin resistance, hyperlipidemia, and visceral fat accumulation, all of which are known risk factors for the development of conventional hepatic steatosis because of the imbalance of sex hormone metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with previous reports revealing that postoperative hepatic steatosis after PD occurs more commonly in females and that females with hepatic steatosis may have a poor response to PERT with high-dose pancrelipase. 20,24 Overall, according to population-based studies, conventional hepatic steatosis is more common in men; however, women have a higher risk of advanced fibrosis. 36 Previous epidemiological studies revealed that postmenopausal women have increased risks of insulin resistance, hyperlipidemia, and visceral fat accumulation, all of which are known risk factors for the development of conventional hepatic steatosis because of the imbalance of sex hormone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that the risk factors for hepatic steatosis after PD were the primary disease of PDAC, the pancreatic resection line, and the remnant pancreatic volume. 16,17,24 Pancreatic ductal adenocarcinoma in the pancreatic head may cause gradual obstruction of the main pancreatic duct and subsequent atrophic changes in the pancreatic body and tail. Therefore, after PD for cancer of the head of the pancreas, the remnant pancreas is usually atrophic with attenuated endocrine and exocrine function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] When we studied the evolution of pancreas endocrine function using GTI instead of DM, GTI was observed to increase significantly during the immediate postoperative period, which probably reflects acute glucose tolerance deterioration due to operation, inflammation, and infection. [29] At 7 days postoperatively, when most patients resumed oral intake, indulged in active exercise, and systemic inflammation was under control, GTI decreased significantly, and subsequently remained stable. The favorable GTI profile after the immediate postoperative period was observed mainly in the PD group, presumably because more pancreas parenchyma is preserved after PD [14] and more α-cells remain.…”
Section: Discussionmentioning
confidence: 99%
“…[10] When we studied the evolution of pancreas endocrine function using GTI instead of DM, GTI was observed to increase significantly during the immediate postoperative period, which probably reflects acute glucose tolerance deterioration due to operation, inflammation, and infection. [29] At 7 days postoperatively, when most patients resumed oral intake, indulged in active exercise, and systemic inflammation was under control, GTI decreased significantly, and subsequently remained stable. The favorable GTI profile after the immediate postoperative period was observed mainly in the PD group, presumably because more pancreas parenchyma is preserved after PD [14] and more a-cells remain.…”
Section: Discussionmentioning
confidence: 92%